Coenzymatic Activity of Pyridoxal 5′-Sulfate and Related Analogues of Pyridoxal 5′-Phosphate - Groman, E. (1972)
The effect of changes in the substituent at the 5′-position of pyridoxal 5′-phosphate on the coenzymatic activity of six analogues of this coenzyme was determined for three bacterial enzymes. Pyridoxal 5′-sulfate showed substantial coenzymatic activity for arginine decarboxylase and tryptophanase, but not for D-serine dehydratase; α(5)-pyridoxalmethylphosphonate showed substantial activity for D-serine dehydratase, but not for the other two enzymes. These results demonstrate that neither the dianionic phosphate group nor the ester oxygen of pyridoxal 5′-phosphate is a general requirement for coenzymatic activity. Minor variations in orientation and charge of the group at position 5 exert major effects on the capacity for complex formation between analogue and apoenzyme, and on the catalytic efficiency of the resulting complex, but have comparatively little effect on the substrate affinity of the analogue-apoenzyme complexes. These effects show no general pattern from enzyme to enzyme, and do not correlate with the affinity of analogue for apoenzyme under the conditions tested.